HUBUNGAN DUKUNGAN KELUARGA DENGAN DEPRESI PENDERITA KUSTA DI RUANG RAWAT PENYAKIT DALAM KUSTA RUMAH SAKIT KUSTA DR. SITANALA TANGERANG - Zahrah Maulidia Septimar; Rista Sembiring (Universitas Yatsi Madani, 2017)
Leprosy is included in one of the infectious diseases with incidence rates still remain high in developing countries, especially in tropical areas. Family support will protect individuals tehadap negative effects of depression and will directly affect an individual's health status. This study design using analytic descriptive method with cross sectional approach. The sampling method used was total sampling with a sample of 35 respondents are diagnosed leprosy patients were hospitalized in internal medicine wards of leprosy hospital Dr. Sitanala Tangerang in August to September 2015. Data were taken using a questionnaire. Data tabulated, analyzed using Chi Square test with a significance level of 0.05. The results showed that of the 21 respondents who have no family support, 19 respondents (90.5%) were depressed, one respondent them suffered from severe depression, and of the 14 respondents who received family support, depressed only 4 (28.5% ), with mild and moderate levels. From the test results obtained by the results of statistical correlation between family support with the level of depression lepers with pvalue value of 0.001 (<alpha = 0.05), using alpha 5% (0.05). Seeing the results of this study need the support of family for lepers to minimize his depression, so that the treatment can be arranged and done well, and the lepers have the spirit to live and socialize in the community.